Psychometric properties of the Beck Depression Inventory‐II in progressive supranuclear palsy. Issue 10 (7th September 2021) - Cuoco, Sofia; Cappiello, Arianna; Abate, Filomena; Tepedino, Maria Francesca; Erro, Roberto; Volpe, Giampiero; Pellecchia, Maria Teresa; Barone, Paolo; Picillo, Marina
Abstract: Objectives: Depression is one of the most common neuropsychiatric symptoms in progressive supranuclear palsy (PSP). Yet, few studies have examined the ability of available instruments to detect depressive symptoms in PSP. Aims of the present study were to (I) report psychometric properties of the Beck Depression Inventory Second Edition (BDI‐II) in PSP, (II) establish the BDI‐II cut‐off indicating the presence of depression in PSP and (III) describe clinical correlates as well as correlation with quality of life of depressive symptoms in PSP. Design, setting and participants: : At the Center for Neurodegenerative Diseases of the University of Salerno, Italy, the BDI‐II was validated in 62 PSP patients diagnosed according to the Movement Disorder Society criteria. Patients underwent a clinical interview, a motor evaluation, extensive cognitive and behavioral testing. Results: The mean BDI‐II total score was 15.92 ± 10.31. The internal consistency was high (Cronbach's alpha = 0.868); corrected item‐total correlation was >0.40 for the majority of items. The significant and moderate correlation of the BDI‐II with other tools evaluating depressive symptoms indicated adequate convergent validity of the scale. The satisfactory cut‐off to identify patients with clinically significant depression was >14.5. We also showed a correlation between higher scores on BDI‐II and lower quality of life, irrespective of motor and cognitive burden. Conclusion: In conclusion, the BDI‐II is a reliable and valid tool for the assessment of depression symptoms in PSP. Such data are useful to standardize studies of depression in PSP and to quantify the effectiveness of any interventions on this disabling symptom. Abstract : We analyzed the psychometric properties of the second version of the Beck Depression Inventory Second Edition (BDI‐II) in a sample of 62 patients with progressive supranuclear palsy (PSP). The BDI‐II showed high internal consistency and good discriminant validity. The satisfactory cut‐off to identify patients with clinically significant depression was 14.5. Depressive symptoms in PSP had a significant impact on quality of life.